2019
DOI: 10.1172/jci.insight.125476
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer precursor immunotherapy for squamous cell carcinoma prevention

Abstract: Conflict of interest: LAC and SD are co-inventors on a filed patent for the use of calcipotriol plus 5-fluorouracil for the treatment of precancerous skin lesions (PCT/US2015/049434).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 26 publications
(43 reference statements)
2
57
0
3
Order By: Relevance
“…The maintenance of T RM reacting with melanoma antigens in the vitiligo lesions, which indicates good prognosis, of melanoma patients [44] at least suggests the protective function of this T RM population against disease development. It has also been reported that T RM induction in actinic keratosis prevents the development of squamous cell carcinoma, demonstrating the antitumor efficacy of TIL with the T RM phenotype [50]. Further functional analyses are needed.…”
Section: Solid Skin Cancersmentioning
confidence: 99%
“…The maintenance of T RM reacting with melanoma antigens in the vitiligo lesions, which indicates good prognosis, of melanoma patients [44] at least suggests the protective function of this T RM population against disease development. It has also been reported that T RM induction in actinic keratosis prevents the development of squamous cell carcinoma, demonstrating the antitumor efficacy of TIL with the T RM phenotype [50]. Further functional analyses are needed.…”
Section: Solid Skin Cancersmentioning
confidence: 99%
“…A 2e4 weeks course appeared to have a protective effect for one year, with non-significant effect thereafter. Addition of calcipotriol to 5-FU has been shown to increase the benefit [179]. Topical tretinoin has no significant effect in preventing cSCC [180].…”
Section: Chemopreventionmentioning
confidence: 99%
“…The 5-FU/calcipotriene combination has previously been shown in mouse models to stimulate expression of thymic stromal lymphopoietin and synergistically activate CD4 + T cell-mediated immunity against actinic keratoses, thereby reducing the incidence of squamous cell carcinoma in treated areas. 4 , 5 Topical 5- FU/calcipotriene has also been reported as an effective treatment option for refractory extramammary Paget disease, presumably through a similar synergistic activation of T cell anti-tumor immunity. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, by generating T cell-mediated immunity against actinic keratoses, topical 5-FU/calcipotriene is thought to potentially establish an anti-tumor immune memory via skin-resident T cells, thereby affording long-term skin cancer suppression. 5 Indeed, Rosenberg et al found that 5-FU/calcipotriene prevented squamous cell carcinoma development on the face and scalp within 3 years after treatment. 5 While this case demonstrates the efficacy of topical 5-FU/calcipotriene in stimulating a localized immune response to successfully treat PM in an immunocompromised patient, it would be helpful to determine whether this combination similarly reduces skin cancer development in this high-risk population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation